Transient Ischemic Dilatation during Stress Echocardiography: An Additional Marker of Significant Myocardial Ischemia. Issue 8 (3rd April 2016) - Kataoka, Akihisa; Scherrer‐Crosbie, Marielle; Senior, Roxy; Garceau, Patrick; Valbuena, Silvia; Čelutkienė, Jelena; Hastings, Jeffrey L.; Cheema, Asim N.; Lara, Alfonso; Srbinovska‐Kostovska, Elizabeta; Hessian, Renee; Poggio, Daniele; et al.
Abstract : Aim: Left ventricular (LV) transient ischemic dilatation (TID) is not clear how it relates to inducible myocardial ischemia during stress echocardiography (SE). Methods and Results: Eighty‐eight SEs were examined from the site certification phase of the ISCHEMIA Trial. LV end‐diastolic volume (EDV) and end‐systolic volume (ESV) were measured at rest and peak stages and the percent change calculated. Moderate or greater ischemia was defined as ≥3 segments with stress‐induced severe hypokinesis or akinesis. Optimum cut points in stress‐induced percent EDV and ESV change that identified moderate or greater myocardial ischemia were analyzed. Analysis from percentage distribution identified a > 13% LV volume increase in EDV or a > 9% LV volume increase in ESV as the optimum cutoff points for moderate or greater ischemia. Using these definitions for TID, there were 27 (31%) with TIDESV and 12 (14%) with TIDEDV . By logistic regression analysis and receiver operating characteristic curves, the percent change in ESV had a stronger association with moderate or greater myocardial ischemia than that of EDV change. Compared to those without TIDESV, cases with TIDESV had larger extent of inducible wall‐motion abnormalities, lower peak stress LVEF, and higher likelihood of moderate or grater ischemia. For moderate or greater myocardial ischemia detection, TIDESV had a sensitivity of 46%, specificity of 83%, positive predictive value of 70%, and negative predictive value of 64%. Conclusion: Transient ischemic dilatation by SE is a marker of extensive myocardial ischemia and can be used as an additional marker of higher risk.